Synthesis, characterization and photocatalysis of heterostructure AgBr/Bi2WO6nanocomposites - Sittikorn Jonjana (2018)
© 2018 Elsevier B.V. 0–15 wt% AgBr/Bi 2 WO 6 nanocomposites used as visible-light-driven photocatalysts were successfully synthesized by a deposition-precipitation method. X-ray diffraction (XRD), transmission electron microscopy (TEM), high resolution transmission electron microscopy (HRTEM) and X-ray photoelectron spectroscopy (XPS) revealed the presence of cubic AgBr nanospheres supported on orthorhombic Bi 2 WO 6 nanoplates. Their photocatalytic performance was investigated through the degradation of rhodamine B (RhB) under visible-light irradiation within 40 min. In this research, 10 wt% AgBr/Bi 2 WO 6 nanocomposites has the highest photocatalytic performance of 99.83% and are the promising material used for removal of contaminants in wastewater.